Nursing Interventions in the Clinical Practice of an Intensive Care Unit (Revista Latino-Americana de Enfermagem, 2010)
This cross-sectional study was carried out at a university hospital to describe the nursing interventions most frequently performed in the clinical practice of an intensive care unit, based on nursing care prescriptions, and to investigate their similarity to the Nursing Interventions Classification (NIC). The sample consisted of 991 hospitalizations of patients. Data were retrospectively collected from the computer database and analyzed through descriptive statistics and cross-mapping. A total of 57 different NIC interventions frequently used in the unit were identified; most of them in the complex (42%) and basic physiological (37%) domains, in the classes respiratory management and self-care facilitation. Similarity between the nursing care prescribed and nursing interventions/NIC was found in 97.2% of the cases. The conclusion is that the interventions/NIC used in the clinical practice of this intensive care unit reflects the level of complexity of nursing care, which is mainly directed at the regulation of the bodys physical and homeostatic functioning.